EFFECT OF FRESH FEED AND DENSITY TO THE SURVIVAL RATE OF JUVENILE MANGROVE CRAB SCYLLA SERRATA - Djoko Suprapto (JOURNAL OF COASTAL DEVELOPMENT, 2001)
The problem of seed production of Scylla serrata juvenile is the massive mortality due to cannibalism among them that normally happen when the animal undergone the molting. The density of juvenile and the feed play important role to avoid the cannibalism. The aim of the study is to understand the interaction between fresh feed and density in controlling the mortality of the juvenile reared in the laboratory scale. A factorial plot with three levels of treatments of fresh feed and three levels of juvenile densities was used in this experiment. The fresh feed treatment did not significantly influence either survival rate or growth rate of juvenile. On the other hand, the density strongly influenced the survival rate of juvenile but not to the growth rate.